IMPLEMENTASI CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW) DALAM KASUS EKSPLOITASI SEKSUAL DIGITAL: STUDI KASUS NTH ROOM DI KOREA SELATAN - Madina, Farah; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes South Korea's implementation of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) in handling cases of digital sexual exploitation, with a focus on the Nth Room case study. South Korea ratified CEDAW in 1984 and has adopted a number of regulations such as the Act on the Punishment of Sexual Violence Crimes and cybercrime policies. However, the findings of this study indicate a gap between normative commitments and their implementation. The main obstacles are weak law enforcement, regulatory delays in responding to developments in digital technology, and institutional bias and patriarchal culture that still influence the treatment of victims. This research was conducted through document analysis, CEDAW Committee reports, legislation, and the Nth Room case study. It was found that the effectiveness of South Korea's policies is partial, in that there has been progress in terms of legislation and public awareness, but this has not been accompanied by the technical capacity building, inter-agency coordination, and social transformation required by CEDAW. This study result emphasizes the need to strengthen the digital legal framework, increase the accountability of technology platforms, empower civil society to realize comprehensive protection of women's rights and manifest the CEDAW’s principals within the CEDAW Committees recommendation for South Korea. Keywords: CEDAW, digital sexual exploitation, South Korea, Nth Room, gender policy.